Performance of hyaluronic acid filler in the anatomization of thin lips: case report - Maria Luiza da Matta Felisberto Fernandes; Mônica Oliveira Mangelli de Souza; Pedro Henrique Rocha Carvalho; Marcela Marçal Thebit; Allyson Henrique de Andrade Fonseca (RGO: Revista Gaúcha de Odontologia)
ABSTRACT The goal of this study is to describe the effect of hyaluronic acid filler on thin lips, evaluating the distribution of the material and its relationship with tissue vascularization, as well as the effectiveness of structuring tissue shape and volume through the immediate clinical results achieved. In addition, this study observes the longevity of the results for a period of 10 months after performing this intervention on the lips. Methodology: A healthy 40-year-old Caucasian woman, complaining of thin lips and who had never undergone clinical or surgical procedures on her lips, participated in this study. An analysis of the lip vascularization and distribution of the filler material in the tissues was carried out using ultrasound images. The adequacy of volume, contour, lip hydration and patient satisfaction were also analyzed. Results: To achieve the desired lip profile, 3 ml of filler material was used throughout 4 sessions. Botulinum toxin therapy was applied to control the depressant muscle forces of the angle of the mouth, the orbicularis oris muscle, and the tip of the nose. A small amount of filler material was used at the tip of the nose to harmonize the facial profile. Conclusions: Thin lips required larger volumes of filler material, which was considered safe and effective if the vascularization is monitored to decide on the best insertion plan for the filler material. A combination with complementary therapies, such as the use of botulinum toxin, may be recommended for the effectiveness of the contour and shape of this lip pattern.